Comparação entre coletas de sêmen em gato-do-mato-pequeno (Leopardus guttulus) pelos métodos de cateterismo uretral e eletroejaculação - Iglesias, Gabriella Accardi (2019)
Habitat reduction and fragmentation put at risk endangered wild cat populations, leading to a decrease in genetic variability. Considering the current reality of small wild felids kept in captivity, the objective of this study was to compare urethral catheterization and electroejaculation semen collecting method after anesthesia with ketamine-dexmedetomidine in L. guttulus in captivity and evaluate the values of volume, concentration, vigor, motility, sperm vitality and acrosomal integrity before and after freezing with the different techniques Initially, 13 animals were used to catheterization semen collecting using ketamine- dexmedetomidine different dosages..After determination of the best anesthetic dose for L guttulus semen collections, the semen was collected by electroejaculation and catheterization method in selected males, and after the descriptive analysis the semen was frozen. The ideal dose for semen collection was 0.008 mg / kg dexmedetomidine. There was a significant difference (p ≤ 0.05) for the concentration variable, according to the collection method. The catheterization method showed higher sperm concentration compared with electroejaculation technique. The results of motility, vigor, pathologies, vitality and acrosome integrity not showed a significant difference (p ≥ 0.05). There was significant difference (p ≤ 0.05) according semen storage, evidencing that the freezing impacts on semen quality in L. guttulus independent of the collection technique used. These results, combined with the advantages of the catheterization method, such as low urine contamination, ease collection and low cost, becoming a promising technique for wild felids, especially those threatened with extinction.